Wild bird - Van Draanen, Wendelin (Ember, 2019)
Fourteen-year-old Wren Clemmens is a girl who has hit rock bottom. Desperate to turn her life around, her parents send her to a wilderness survival camp for eight weeks. Wren's bitterness and anger do nothing to help her when she arrives at the desert camp. Survival there means Wren must accept the consequences of her actions and admit that she is responsible for her current situation.